Are TKA Kinematics During Closed Kinetic Chain Exercises Associated with Patient-reported Outcomes? A Preliminary Analysis. Issue 2 (February 2020) - Van Onsem, Stefaan; Verstraete, Matthias; Van Eenoo, Wies; Van Der Straeten, Catherine; Victor, Jan
Abstract: Background: Kinematic patterns after TKA can vary considerably from those of the native knee. It is unknown, however, if there is a relationship between a given kinematic pattern and patient satisfaction after TKA. Questions/purposes: Is there an association between kinematic patterns as measured by AP translation during open kinetic chain flexion-extension and closed kinetic chain exercises (rising from a chair and squatting) and a custom aggregate of patient-reported outcome measures (PROMs) that targeted symptoms, pain, activities of daily living (ADL), sports, quality of life (QOL), and patient satisfaction after TKA? Methods: Thirty patients who underwent TKA between 2014 and 2016 were tested at a minimum follow-up of 6 months. As three different implants were used, per implant the first 10 patients who presented themselves at the follow-up consultations and were able to bend the knee at least 90°, were recruited. Tibiofemoral kinematics during an open kinetic chain flexion-extension and closed kinetic chain exercises—rising from a chair and squatting—were analyzed using fluoroscopy. A two-step cluster analysis was performed, resulting in two clusters of patients who answered the Knee Injury and Osteoarthritis Outcome Score and the satisfaction subscore of the Knee Society Score questionnaires. Cluster 1 (CL1) consisted of patients with better (good-to-excellent) patient-reported outcome measures scores (high-PROMs cluster); Cluster 2 (CL2) consisted of patients with poorer scores (low-PROMs cluster). Tibiofemoral kinematics were compared between patients in these clusters by performing a Mann-Whitney U test with Bonferroni correction. Results: Concerning open kinetic chain flexion-extension, there was no difference in kinematic patterns between the patients in the high-PROMs cluster and those in the low-PROMs cluster, with the numbers available. However, during the closed-chain kinetic exercises, medially, initial anterior translation (femur relative to tibia) was found in patients in Cluster 1 during early flexion, but in those in Cluster 2, translation was steeper and ran more anteriorly (CL1 -1.5 ± 7.3%; CL2 -8.5 ± 4.4%); mean difference 7.0% [95% CI 0.1 to 13.8]; p = 0.046). In midflexion, the femur did not translate anterior nor posterior in relation to the tibia, resulting in a stable medial compartment in Cluster 1, whereas Cluster 2 had already started translating posteriorly (CL1 -0.7 ± 3.5%; CL2 3.4 ± 3.6%; mean difference -4.1% [95% CI -7.0 to -1.2]; p = 0.008). There was no difference, with the numbers available, between the two clusters with respect to posterior translation in deep flexion. Laterally, there was small initial anterior translation in early flexion, followed by posterior translation in midflexion that continued in deep flexion. Patients in Cluster 1 demonstrated more pronounced posterior translation in deep flexion laterally than patients in Cluster 2 did (CL1 8.3 ± 5.2%; CL2 3.5 ± 4.5%); mean difference 4.9% [95% CI 0.6 to 9.1]; p = 0.026). Conclusions: This study of total knee kinematics suggests that during closed kinetic chain movements, patients with poor PROM scores after TKA experience more anterior translation on the medial side followed by a medial mid-flexion instability and less posterior translation on the lateral side in deep flexion than patients with good PROM scores. The relationship of kinematic variations with patient-reported outcomes including satisfaction must be further elaborated and translated into TKA design and position. Reproduction of optimal kinematic patterns during TKA could be instrumental in improving patient satisfaction after total knee replacement. Future expansion of the study group is needed to confirm these findings. Level of Evidence Level II, therapeutic study.